2013
DOI: 10.1021/ct300765w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grid Spacing in Poisson–Boltzmann Equation Binding Energy Estimation

Abstract: Grid-based solvers of the Poisson-Boltzmann, PB, equation are routinely used to estimate electrostatic binding, ΔΔGel, and solvation, ΔGel, free energies. The accuracies of such estimates are subject to grid discretization errors from the finite difference approximation to the PB equation. Here, we show that the grid discretization errors in ΔΔGel are more significant than those in ΔGel, and can be divided into two parts: (i) errors associated with the relative positioning of the grid and (ii) systematic error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 26 publications
3
36
2
Order By: Relevance
“…Scale dependence is an important feature for PB solvers implemented in the finite difference method 40, 41 . In previous work, we demonstrated that the Gaussian method performs better on grid shift error and rotation error compared to the homogeneous method 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Scale dependence is an important feature for PB solvers implemented in the finite difference method 40, 41 . In previous work, we demonstrated that the Gaussian method performs better on grid shift error and rotation error compared to the homogeneous method 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The successive over‐relaxation method was used to the solve the equation sets. The grid was reconstructed for each conformation, with the coarse‐grained grid dimensions equal to the longest length of the solute in each dimension plus 20 Å after orienting the molecule to place the principle geometric axis on the x ‐axis and the next largest axis on the y ‐axis, with a resolution of 1 Å; the fine‐grained grid had instead only an additional 5 Å added to each dimension, and a resolution of 0.2 Å (the more commonly used 0.5 Å has been found to be insufficient in many cases). The definition of the boundary between solute and solvent was that by Nina et al with a half width of the transition region of 0.3 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we calculated the binding free energies for several DNA‐drug complexes from previous studies via our PBE and NMPBE solvers. It is interesting to find that a slope of the best‐fit line to the binding free energies predicted by NMPBE can match the experiment data better than those by PBE (see Figures 3 and 7 and Table 5), further indicating that NMPNE is a valuable variant of PBE.…”
Section: Introductionmentioning
confidence: 99%